2020
DOI: 10.34172/jrhs.2020.09
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Students' Flu Vaccine Uptake in the Last 5 Years and Future Vaccination Acceptance: Is There a Possible Association?

Abstract: Background: Despite the free-of-charge offer of influenza vaccines to at-risk subgroups, vaccine coverage remains low and far from the target, probably due to the false myths and misperceptions. We aimed to explore the healthcare students’ vaccination behavior and beliefs to find any association between vaccination uptake during the last 5 years and future vaccination acceptance. Study design: A multicentre cross-sectional study. Methods: From Oct 2017 to Nov 2018, the Italian healthcare students from 14 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Medical students, having similar contact with patients as HCWs, are also an important target group for annual influenza vaccinations. If people are motivated to receive vaccinations as students, they are likely to continue being vaccinated as HCWs in the future [ 11 ]. Studies show that vaccination coverage among medical students ranges from 4.7% in Iran to 86.3% in Canada (in various seasons) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical students, having similar contact with patients as HCWs, are also an important target group for annual influenza vaccinations. If people are motivated to receive vaccinations as students, they are likely to continue being vaccinated as HCWs in the future [ 11 ]. Studies show that vaccination coverage among medical students ranges from 4.7% in Iran to 86.3% in Canada (in various seasons) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 40 studies included in our systematic review [ 3 , 4 , 5 , 8 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], seven (17.5%) had a non-European perspective and were conducted in Canada ( n = 1) [ 18 ], the USA ( n = 3) [ 19 , 21 , 42 ], China ( n = 1) [ 36 ], Iran ( n = 1) [ 49 ], and low-income countries (LICs) ( n = 1) [ 32 ]; ten (25%) had a global perspective [ 5 , 10 , 12 , 20 , 22 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Among the European studies, eight (36.4%) were conducted specifically in Italy [ 3 , 4 , 13 , 31 , 38 , 39 , 43 , 47 ]. In addition, of the 40 articles included in our work, 17 (42.5%) were systematic reviews or literature reviews [ 3 , 5 , 10 , 11 , 12 , 22 , 24 , 25 , 28 , 29 , 30 , 31 , 32 , 37 , 41 , 47 , 48 ], ten (25%) were economic evaluations [ 8 , 13 , 19 , 21 , 23 , 26 , 27 , 34 , 44 , 45 ], seven (17.5%) were cross-sectional studies [ 18 , 35 , 36 , 38 , 42 , 43 , 49 ], two studies (5%) were HTA reports [ 4 , 39 ], one study (2.5%) was a nonlinear regression model [ 33 ], and three studies (7.5%) were expert opinions [ 20 , 40 , 46 ]. The main features of the studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations